.44x+.07(x+7)=4.57

Simple and best practice solution for .44x+.07(x+7)=4.57 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .44x+.07(x+7)=4.57 equation:


Simplifying
0.44x + 0.07(x + 7) = 4.57

Reorder the terms:
0.44x + 0.07(7 + x) = 4.57
0.44x + (7 * 0.07 + x * 0.07) = 4.57
0.44x + (0.49 + 0.07x) = 4.57

Reorder the terms:
0.49 + 0.44x + 0.07x = 4.57

Combine like terms: 0.44x + 0.07x = 0.51x
0.49 + 0.51x = 4.57

Solving
0.49 + 0.51x = 4.57

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.49' to each side of the equation.
0.49 + -0.49 + 0.51x = 4.57 + -0.49

Combine like terms: 0.49 + -0.49 = 0.00
0.00 + 0.51x = 4.57 + -0.49
0.51x = 4.57 + -0.49

Combine like terms: 4.57 + -0.49 = 4.08
0.51x = 4.08

Divide each side by '0.51'.
x = 8

Simplifying
x = 8

See similar equations:

| 100+25w=400 | | 1.2r+2(3.4r-1)=1.4r+6 | | 16-45=4(x-2)-9 | | b=c+24 | | -8y+3y-(10)+2y=11 | | 5+(n+9)=-3 | | 15=2t+.806t | | 25+50h=8 | | 3y^2+27y+60=0 | | 3(x+2)-10(x+10)=-7-8 | | 4t=2(7x+15) | | 6(3x+7)=3x+2-5x | | 3+5h=5 | | 10(x-2)=2(x+9) | | 34-0.5d=26 | | 2.1(a+2)=2.1a+4.2 | | 4-4(x-2)=-1+3(x-5+2) | | 3n-6-6+2n=4n-12 | | 0=-4x+21-x^2 | | 2x(5.83)=x(5.83) | | 5x=8(6x-1)-35 | | 4x^3+12x^2+2=0 | | 11-(-10)-5/6= | | 4[2-3(2x+4)]=5x | | (y-6)-(5y-7)= | | log(x)=1.9 | | y=9x^2-36 | | -40=6x+8 | | 5(1x+7)=20 | | (y-5)-(5y-7)= | | 3x+10=15x-8 | | 5(-2x+8)=-50 |

Equations solver categories